The social representation of teaching in basic education geography - Mendes, Larissa Sousa; Silva, Josélia Saraiva e (Geosaberes; Vol 10 No 21 (2019): May - August, 2019)
Literature and research on the social significance and attractiveness of the teaching career in Brazil have shown a growing devaluation of this profession, especially being a teacher of school geography. This is because Geography was introduced in school curriculum as a theoretical tool of recognition of the national territory, as well as with the intention of integrating the nation-state and protecting its borders. Because of this scenario, this discipline prioritized the description and characterization, mainly of physical aspects, of places and their respective populations, for a long time. Thus, despite having developed a rich theoretical-methodological framework, with which we began to observe the geographic space from other angles, Geography has until today, in common sense, the stigma of being an encyclopedic school discipline, which has little relation to daily life, and that, therefore, requires the students of Basic Education with an exacerbated effort of memory. In order to contribute to this discussion, the present article aims to approach this theme from the Theory of Social Representations (MOSCOVICI, 1969). From this perspective we seek to identify  the theoretical references, already existing questions that deal with the initial formation and the construction of a social representation of the condition of being professor of Geography in Brazil. To support this discussion, we use as theoretical reference authors such as Tardif (2002), Nóvoa (1997), Callai (2003) Pontuschka (2009, 2010), among others. Thus we infer the existence of a geography school that inserted it in an uncritical view of reality, even though its theoretical discourse directs it to the opposite direction.